Observational study of vaginal culture in symptomatic and asymptomatic non pregnant female patient in tertiary care hospital - Chandanan, Ani; Arora, Mamta; Arora, Swati; Mishra, Shalini; Malik, Annu; Kumari, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Vaginal miroflora plays an important role in maintaining healthy microenvironment. Lactobacilli are the dominant flora responsible for this. Any disturbance in balance of normal and abnormal flora leads to different types of vaginal infections like, vulvo-vaginal candidiasis, and bacterial vaginosis. Most common organisms causing vaginitis is Gardnerella vaginalis which causes bacterial vaginosis. Other organisms responsible for infections are, candida, trichomonas, and viruses. Abnormal growth of pathogenic bacteria during pregnancy can lead to various adverse pregnancy outcomes. Methods: This is an observational study conducted in a tertiary care hospital over a period of 6 months (January 2023 to June 2023). Overall, out of 135 women, sample of 120 women were taken and treated accordingly. Results: Among 120 women, 52 (43.3%) women had no growth on culture, while 20 patients (16.6%) showed growth of Klebsiella and 20 (16.6%) patient shows Candida and rest shows growth of other pathogen. Conclusions: In our study, half of the women were found to be with positive culture report, who shown improvement after treatment.